Trophic states assessed from abundance of phythoplankton and chlorophyl-a content in Raman Resevoir Metro, Lampung Province - Aulia Insani; Herman Yulianto; Putu Cinthia Delis (Tomini Journal of Aquatic Science, 2021)
Raman reservoir is located at north of Metro City, Lampung. The water resources of the reservoir comes from Way Bunut and Way Raman rivers. The Way Bunut and Way Raman rivers flow into the Raman reservoir which is used for a variety of human activities, including fish farming with the floating net cage system, tourism, and agriculture. These activities produce organic and inorganic materials into the waters so that it may cause changes in water quality and trophic states levels, therefore research is carried out on the trophic states based on the abundance of phytoplankton and chlorophyll-a content in the waters of the Raman Reservoir. The purpose of this study was to assess the trophic states of the Raman Reservoir based on the abundance of phytoplankton, chlorophyll-a concentration, and Nygaard Index. This research was conducted in January-March 2020. The data was collected using purposive sampling method. The parameters used in this study were abundance of phytoplankton, chlorophyll-a, primary productivity, brightness, depth, temperature, DO, pH. Trophic states results based on the concentration of chlorophyll-a in the morning range from 0.0007 - 0.0274 mg/L while at noon it ranges from 0.0083-0.0769 mg/L. The results of these measurements can be categorized as chlorophyll-a content in Raman Resevoir was still in the category oligotrophic. The results of trophic states based on the Nygaard index it shows the category of eutrophic.